of (a + i6) ^5= a +iB the (b+ ia) is equal to
Answers
Answered by
1
Answer:
Step-by-step explanation:
Given,
(a+ib)
5
=α+iβ
or, i
5
(b−ai)
5
=α+iβ [ Taking i common from the right hand side]
or, i(b−ai)
5
=α+iβ [ Since i
4
=1]
or, (b−ai)
5
=β−iα [ Multiplying both sides with −i]
Now taking conjugate both sides we get,
(b+ia)
5
=β+iα. [ Since
z
5
=
z
5
].
Answered by
1
Answer:
Given,
(a+ib)
5
=α+iβ
or, i
5
(b−ai)
5
=α+iβ [ Taking i common from the right hand side]
or, i(b−ai)
5
=α+iβ [ Since i
4
=1]
or, (b−ai)
5
=β−iα [ Multiplying both sides with −i]
Now taking conjugate both sides we get,
(b+ia)
5
=β+iα. [ Since
z
5
=
z
5
].
please mark me at brainlist
Similar questions